Layanan Bimbingan Dan Konseling Daring Selama Masa Pandemi Covid-19 - Putri, Vany Dwi (Coution: Journal Counseling and Education, 2020)
In the early 2020, the world was shocked by the corona outbreak virus (Covid-19) which infected almost all countries in the world. In Indonesia, the Government issued an emergency status from 29 February 2020 to 29 May 2020 related to the corona virus pandemic with a total time of 91 days. Bold learning instructed by the government is also determined in the provision of guidance and counseling programs. Student learning activities are directed in the form of online learning or online at home. Online learning activities are basically very diverse, among others, can be carried out through google classroom, zoom, educational tv, interactive learning in the home learning portal, Ruang Guru and other online learning applications The difference between guidance and counseling programs with other subjects is, guidance and counseling programs do not provide materials or assignments that burden students. Guidance and counseling programs provide learning through meaningful formats for students. Abstrak Pada awal tahun 2020, dunia dikejutkan dengan wabah virus corona (Covid-19) yang menginfeksi hampir seluruh negara di dunia. Di Indonesia, Pemerintah telah mengeluarkan status darurat bencana terhitung mulai tanggal 29 Februari 2020 hingga 29 Mei 2020 terkait pandemic virus corona dengan jumlah waktu 91 hari. Pembelajaran daring yang diinstruksikan oleh pemerintah juga ditetapkan dalam pemberian layanan bimbingan dan konseling. Kegiatan pembelajaran siswa diarahkan dalam bentuk pembelajaran secara daring atau online di rumah. Kegiatan pembelajaran secara daring ini pada dasarnya sangat beragam, antara lain dapat dilaksanakan melalui google classroom, zoom, tv edukasi, belajar interaktif di portal rumah belajar, ruang guru dan aplikasi belajar online lainnya Perbedaan layanan bimbingan dan konseling dengan materi pelajaran lain adalah, layanan bimbingan dan konseling tidak memberikan materi-materi ataupun tugas-tugas yang memberatkan siswa. Layanan bimbingan dan konseling menyajikan layanan dalam pembelajaran daring melalui format yang bermakna bagi peserta didik